Defending Antipodean economic geography. (July 2013) - Wray, Felicity; Dufty-Jones, Rae
In response to the commentaries, we reflect on the pitfalls and opportunities that come with identifying and naming 'Antipodean economic geographies' and in particular emphasise the practical aspects of this decision. We also critically reflect on suggestions that we have brought such knowledges into a set of market relations, citing how the recently published International Benchmarking Review of UK Human Geography gives added salience to the intentions of our original paper. Finally, we note the useful ground clearing that these commentaries make for future debates around the politics and whereness of economic geographical knowledge production in new global contexts.